Monitoring the anthropogenic impacts in Admiralty Bay using meiofauna community as indicators (King George Island, Antarctica) - GHELLER,PAULA F. (2022)
Abstract Activities at the Brazilian Antarctic Station (EACF) may cause damage to surrounding environment. Meiofauna was used to evaluate this impact. One area possibly impacted by the stations’ presence (CF) and a reference area (BP) were compared. Sediment samples for meiofauna and environmental variables were obtained in two periods, at two sites and depths in each area. Densities were higher at 20-30m and nematodes were the dominant taxa (90%). Nematode densities ranged from 1,278±599 (BP1 50-60m) to 16,021±12,298 ind.10 cm-² (BP2 20-30m). A total of 68 genera were found. Sample richness ranged from 8 to 26 and diversity from 1.4 to 3.6 bits/ind, both being higher at BP 50-60m, where dominance of epistrate feeders was lower. Selective and non-selective deposit feeders were codominant with similar proportions. Maturity index was high and constant between samples. Aponema, Sabatieria, Daptonema, Dichromadora and Halalaimus were dominant, with higher densities at 20-30m. In contrast, Actinonema, Molgolaimus, Oxystomina and Marylynnia were more abundant at 50-60m. Differences in meiofauna community were found mainly between depths, but not between sites or periods, suggesting no anthropogenic impact. Nevertheless, lower Nematoda diversities and maturity index at 50-60m in CF when compared to BP may indicate a possible anthropogenic effect near EACF.